Deteksi Potensi Resiko Kecurangan pada Laporan Keuangan dengan Menguji Pengaruh Kualitas Audit, Size, Leverage dan Financial target terhadap Manajemen Laba Riil - ., Indarti (Institut Bisnis dan Informatika Kesatuan, 2017)
This study is purposed to detect the potential risk of fraud in financial statements by examining the influence of audit quality, firm size, leverage, and financial target on real profit management. Audit quality in this study is measured by grouping Public Accountant Office into Big Four and Non Big Four and Auditor industrial specialization. Firm size is measured using Total Assets, Leverage and Financial Targets. The data used in this research are secondary sourced from the financial statements of manufacturing companies listed in the Indonesia Stock Exchange during 2012-2014. Using purposive sampling, there will be taken some samples to use. Data analysis method used is multiple linear regression tests using SPSS version 20. The samples selected based on purposive sampling method with population of 134 companies and a sample of 21 companies. Analysis technique methods used are descriptive statistic analysis, classical assumption test, F-statistic hypothesis test to examine the influence altogether with 5% level of accountability, and to test the partial coefficient regression, we used t-statistic test. The results show that Audit Quality, Firm Size, Leverage and Financial Targets significant.ly influence the fraud on financial statements with Real Profit Management proxy. Mean while, Audit Quality and Leverage have partial significant influences on financial statements frauds.